Kewajiban Indonesia Berdasarkan Ketentuan Yang Bersamaan Konvensi Jenewa 1949 - Erlies S. Nurbani (Jatiswara, 2018)
As a part of international community, which had ratify various of international agreements, Indonesia obliged to create national laws which compatible with international agreements. Since ratification of international agreements is not a final process which must comply by a state to abide the international agreements. The adjusment of national law whether with establish the new law or amendment the existed law, is repercussions of ratifications phase which state have to fulfill. One of Indonesia obligations, based on Geneva Conventions 1949 for the Protection of Victims of War, i.e common articles of Article 49 Geneva Convention I, Article 50 Geneva Convention II, Article 129 Geneva Convention III and Article 146 Geneva Convention IV is to establish national law on grave breaches of the convention and to prosecute the perpetrators. This article try to examine further on the Indonesia obligations based on th common articles and its implementaion in Indonesia, after 60 years of Indonesia accesion to the Geneva Conventions 1949 with the Law Number 59 Year 1958 on Indonesia Participation on all of Geneva Conventions 1949.